PENDUGAAN MODEL ANOMALI MAGNETIK BAWAH PERMUKAAN DESA DARMAKRADENAN, KECAMATAN AJIBARANG, KABUPATEN BANYUMAS - Sehah, Sehah; Raharjo, SUkmaji Anom (BERKALA FISIKA, 2013)
Magnetic survey has been carried out to estimate the subsurface magnetic anomaly model inDarmakradenan Village, Ajibarang District, Banyumas Regency. After the data processing whichincludes some corrections and reductions, then obtained the residual magnetic anomaly data in theresearch area. Then this magnetic anomaly data was modeled use Mag2DC for Windows software,thus obtained four subsurface anomalous objects, which are interpreted as coarse grained sandstones,Â conglomerates, and andesitic breccias from Tapak Formation (Ï‡ = 0.0055 cgs units), lava depositionof Slamet Volcano; with boulder of basaltic-andesite from old Slamet Volcano eruption (Ï‡ = 0.0175Â cgs units), andesitic sandstone, tuff conglomerate, and marl which insert of sandstone from HalangFormation (Ï‡ = 0.0015 cgs units), and limestones from Tapak Formation (Ï‡ = 0.0035 cgs units). TheÂ research areas have natural resources of limestone that is being cultivated mining now. While thepresence of gold minerals can not be determined, but is expected in the old alluvial deposits of TapakFormation and Halang Formation.Keywords: Magnetic anomaly, subsurface, Darmakradenan Village